Investigation of the relationship between investment and the profit of tradespeople in Qala-e-Naw city, Badghis province, in 2023 - Safiullah Safa Afzaly; Mohammad Osman Rahmani; Sayed Hamid Sayqal (Science and Education, 2024)
Management of working capital is an important issue in the field of financial management and accounting. Proper utilization working capital of components and making optimal decisions and implementing policies in this regard can significantly enhance a company’s profitability indirectly. (Arshiannejad et al., 2017). Working capital highly influences a company’s profitability, risk and sometimes affects its continuity. Implementing suitable working capital management and preventing cash resource constraints improve performance and profitability, as result it can add the value of a company (Arshiannejad et al., 2018). Increasing household savings inclination by 20% has resulted in a corresponding 20% increase in their savings, yet it has concurrently led to reduced household consumption (Shahreki et al., 2010). Tradespeople in markets act as distribution channels, purchasing goods from producers and making them available to consumers. The activity and income generation of this market segment signify market vitality, demand sustainability, and investment potential. Absence of tradespeople implies lack of production, supply, demand, and investment. This research, conducted in the year 2023 AD, aimed to investigate the relationship between investments and the profit of tradespeople in Qalai Naw City, Badghis Province, using a questionnaire distributed to a sample of 381 randomly selected tradespeople. Data analysis was performed using SPSS version 25. The findings indicate that increasing investments lead to increased profit for tradespeople in Qalai Naw City. The relationship between investment and tradespeople’s profit is positive, with a correlation coefficient of 0.35, meaning that a one-unit increase in investment results in a 0.35-unit increase in profit for tradespeople. Additionally, there is a weak positive relationship (0.48) between investment and cost of tradespeople, while a strong positive relationship (0.52) exists between investment and gross income of tradespeople.